Regionalism and Rivalry : Japan and the U.S. in Pacific Asia. - Frankel, Jeffrey A. (National Bureau of Economic Research conference report., 1993)
As Japan's newfound economic power leads to increased political power, there is concern that Japan may be turning East Asia into a regional economic bloc to rival the U.S. and Europe. In Regionalism and Rivalry, leading economists and political scientists address this concern by looking at three central questions: Is Japan forming a trading bloc in Pacific Asia? Does Japan use foreign direct investment in Southeast Asia to achieve national goals? Does Japan possess the leadership qualities necessary for a nation assuming greater political responsibility in international affairs?. The authors c.